If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -6 = 68 Reorder the terms: -6 + 6n = 68 Solving -6 + 6n = 68 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6n = 68 + 6 Combine like terms: -6 + 6 = 0 0 + 6n = 68 + 6 6n = 68 + 6 Combine like terms: 68 + 6 = 74 6n = 74 Divide each side by '6'. n = 12.33333333 Simplifying n = 12.33333333
| (6x-5)(6x+5)=12 | | Z+(-3)=4 | | 3(10-2x)-12=-2(x-11)+4 | | 0/0=0 | | 10z-10=4z+20 | | 3(x-4)+9=-2 | | x/4-812 | | x^5-2x^4-8x^3+20x^2+15x-50=0 | | 2/fs=18 | | 6r=32 | | 4(b-2)10=2(b+3) | | -8w+4(w-4)=12 | | -3(x+9)+7x=49 | | 3z-2=z+12 | | X/80=3/20 | | Y=-16t(2)+96t+3 | | -2z-1=z+2 | | (4u+5)(8+u)=0 | | 9X-15-2X=-60+9 | | 9=d/-3 | | -2z-1=-z+2 | | 2(4x+3x)+6=32 | | f(3)=252-15x | | 12.6+4m=9.6+8m | | f(x)=252-15x | | (7b-2)-5(7b+8)=-56 | | 1/6x1/6x1/6x1/6x1/6 | | 16-2t=1.5t+9 | | -x^2=-4x-5 | | 1=5-4p-8 | | x+72=9x | | 4(x-8)+2=2(x-4) |